The strength of the silicon die in flip-chip assemblies - Chen, Z. (2012)
The mechanical reliability of silicon dies is affected by the defects introduced by surface grinding and edge dicing. The ring-on-ring and the four-point-bend test have been used in this study to separate the distribution in strength for these two types of defect. At low probabilities of failure, it is the "strength" of the edge defects that dominate the reliability. However, if the edges of the die are only lightly stressed compared with the surface, edge defects are unlikely to cause fracture. In this case the use of the four-point-bend test, which is sensitive to both edge and surface defects, will result in an underestimate of the reliability and if only one test is to be performed the ring-on-ring test is preferable to the four-point-bend test. Generally, for a full reliability estimate, the distributions of both types of defect need to be determined.